Postać i dzieło św. Alberta Chmielowskiego widziane oczyma malarzy - Pyczek, Ewa (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Adam Chmielowski’s artistic output has not been made widely known up to now, although the reports of his contemporary artists as well as the ones of later generations prove that in many respects he was a precursor of impressionism and symbolism in the history of Polish art – both in his artistic works and the theoretical ones („About the Essence of Art”). He was an outstanding colourist focused upon the aesthetic and emotional aspects of scenery; his landscapes of pronounced synesthetic values ( rhythm, harmony, feeling; repeated motifs, colour schemes) invite the viewers to contemplation.